Ext1 heterozygosity causes a modest effect on postprandial lipid clearance in humans[S] - Mooij, Hans L.; Bernelot Moens, Sophie J.; Gordts, PhilipL.S.M.; Stanford, KristinI; Foley, ErinM; van den Boogert, MarjoleinA.W.; Witjes, JuliaJ; Hassing, H.Carlijne; Tanck, MichaelW; van de Sande, MichielA.J.; Levels, J.Han; Kastelein, JohnJ.P.; et al. (Journal of lipid research, 2015)
Elevated nonfasting TG-rich lipoprotein levels are a risk factor for CVD. To further evaluate the relevance of LDL-receptor (LDLr) pathway and heparan sulfate proteoglycans (HSPGs) in TG homeostasis, we analyzed fasting and postprandial TG levels in mice bearing combined heterozygous mutations in both Exostosin (Ext) 1 and Ldlr, in subjects with hereditary multiple exostosis (HME) due to a heterozygous loss-of-function mutation in EXT1 or EXT2 (N = 13), and in patients with heterozygous mutations in LDLR [familial hypercholesterolemia (FH)] and SNPs in major HSPG-related genes (n = 22). Mice bearing a homozygous mutation in hepatic Ext1 exhibited elevated plasma TGs similar to mice lacking other key enzymes involved in HSPG assembly. Compound heterozygous mice lacking Ldlr and Ext1 showed synergy on plasma TG accumulation and postprandial clearance. In human subjects, a trend was observed in HME patients toward reduced postprandial TG clearance with a concomitant reduction in chylomicron clearance [area under the curve (AUC)-retinyl ester (RE) HME, 844 ± 127 vs. controls, 646 ± 119 nM/h, P = 0.09]. Moreover, in FH subjects with a high HSPG gene score, retinyl palmitate excursions were higher (AUC-RE, 2,377 ± 293 vs. 1,565 ± 181 nM/h, P < 0.05). Incremental AUC-apoB48 was similar between the groups. In conclusion, the data are supportive for a minor yet additive role of HSPG in human postprandial TG clearance, and further studies are warranted.